أثر التجارة الإلكترونية على إنتاجية وتنافسية المؤسسة - محمد شايع; وليد رويحة; طارق حمتين; هارون شتحونة (جامعة الوادي university of eloued, 2024)
هدفت الدراسة إلى استقصاء تأثير التجارة الإلكترونية على تنافسية المؤسسات في قطاع الصناعة الكندي، وقد أثبتت النتائج صحة فرضية البحث التي تنص على أن للتجارة الإلكترونية تأثيرًا إيجابيًا على تنافسية المؤسسة من خلال زيادة الحصة السوقية وتحسين الإنتاجية. وقد دعمت هذه النتائج الدراسة الاستطلاعية التي أُجريت على الوكالات السياحية في منطقة الوادي. The study aimed to investigate the impact of e-commerce on the competitiveness of enterprises in the Canadian industrial sector. The results confirmed the research hypothesis that e-commerce has a positive effect on the competitiveness of enterprises by increasing market share and improving productivity. These findings were supported by the exploratory study conducted on travel agencies in the El -Oued area.
Keywords: التجارة الإلكترونية، تنافسية المؤسسات، الحصة السوقية، الإنتاجية، تكنولوجيا المعلومات e-commerce; competitiveness of enterprises; market share; productivity; information technology.